Unravelling the Extent of Diversity within the Iberian Medicinal Leeches (Hirudinea: Hirudo) Using Molecules and Morphology - Andrés Arias; Victor Surugiu; Rafael Carballeira; Oana Paula Popa; Luis Ovidiu Popa; Serge Utevsky (Biology, 2021)
Until the beginning of the 21st century, the famous medicinal leech was thought to be represented by only one species, Hirudo medicinalis. However, recent publications have demonstrated that under that name, at least five different species of medicinal leeches were hidden. During the last decade, the biogeography of Western-Palaearctic leeches has begun to unravel, untangling their diversity in practically all of Europe, except for its westernmost peninsula, Iberia. Hirudo medicinalis has been repeatedly reported from Iberia, but those records were considered questionable. We discovered H. verbana in northern Spain, constituting its first record in Iberia. Using an integrative approach (combining morpho-anatomical data and molecular analyses using three genes, COI,12S rRNA, and ITS2), two endemic and geographically separated Iberian lineages have been found. One of them is easily distinguished by its distinctive colour-pattern and is described as H. verbana bilineata ssp. nov. We characterized the new subspecies morphologically, ecologically, and genetically. We also established its phylogenetic relationships with other European Hirudo spp. and confirm the presence of H. troctina in Iberia, occurring as far as 43° lat. N. Iberian H. verbana records constitute its westernmost known distribution to date. The provided distribution pattern of H. verbana contributes to a better understanding of the complexity of Iberia as a glacial refugium/cradle for endemisms, harbouring populations with a high degree of genetic structure that began to settle throughout the Pleistocene. Iberian Hirudo populations are declining in recent decades and there is an urgent need to assess their conservation status and to initiate conservation measures to reverse their decline.